Artificial Intelligence in Writing Skills Development: A Systematic Review of Recent Research and Current Effects - Pradana Gilang Perkasa; Vina Qurrota’ Akyuningrum; Aminnatun Sadiyah (Universitas Tidar, 2025)
The rapid adoption of artificial intelligence (AI) tools such as ChatGPT, Grammarly, and QuillBot has transformed writing instruction. It remains that their long-term educational effects still unclear. This study conducts a systematic qualitative review of 23 peer-reviewed articles published between 2024 and 2025. This study synthesizes current research on AI’s role in writing skill development. The analysis identifies four major trends: (1) AI tools consistently improve surface-level writing quality; (2) learners with higher AI literacy use these tools more efficient; (3) ethical challenges, such as plagiarism and fairness, necessitate clear institutional policies; and (4) contextual factors, including educational level and teacher mediation, strongly influence AI’s effectiveness. Overall, the findings in this study reveal that AI enhances linguistic accuracy and learner confidence. However, it also reveals that it contributes little to higher-order writing abilities like coherence and critical thinking. These results suggest that hybrid feedback models where teacher and AI work together offer the most pedagogically sound approach. The review concludes that responsible AI integration can transform writing pedagogy while safeguarding creativity and academic integrity.